C-type lectin interacting with β-integrin enhances hemocytic encapsulation in the cotton bollworm, Helicoverpa armigera. (July 2017) - Wang, Pan; Zhuo, Xiao-Rong; Tang, Lin; Liu, Xu-Sheng; Wang, Yu-Feng; Wang, Guo-Xiu; Yu, Xiao-Qiang; Wang, Jia-Lin
Abstract: The encapsulation reaction in invertebrates is analogous to granuloma formation in vertebrates, and this reaction is severely compromised when ecdysone signaling is blocked. However, the molecular mechanism underlying the encapsulation reaction and its regulation by ecdysone remains obscure. In our previous study, we found that the C-type lectin HaCTL3, from the cotton bollworm Helicoverpa armigera, is involved in anti-bacterial immune response, acting as a pattern recognition receptor (PRR). In the current study, we demonstrate that HaCTL3 is involved in defense against parasites and directly binds to the surface of nematodes. Our in vitro and in vivo studies indicate that HaCTL3 enhances hemocytic encapsulation and melanization, whereas H. armigera β-integrin (Haβ-integrin), located on the surface of hemocytes, participates in encapsulation. Additionally, co-immunoprecipitation experiments reveal HaCTL3 interacts with Haβ-integrin, and knockdown of Haβ-integrin leads to reduced encapsulation of HaCTL3-coated beads. These results indicate that Haβ-integrin serves as a hemocytic receptor of HaCTL3 during the encapsulation reaction. Furthermore, we demonstrate that 20-hydroxyecdysone (20E) treatment dramatically induces the expression of HaCTL3, and knockdown of the 20E receptor (EcR)/ultraspiracle (USP), abrogates this response. Overall, this study provides the first evidence of the presence of a hemocytic receptor (Haβ-integrin), that interacts with the PRR HaCTL3 to facilitate encapsulation reaction in insects and demonstrates the regulation of this process by the steroid hormone ecdysone. Graphical abstract: Highlights: HaCTL3 is involved in defense against parasites and directly binds nematodes. HaCTL3 enhances hemocytic encapsulation and melanization. Haβ-integrin serves as a hemocytic receptor of HaCTL3 during the encapsulation. 20E induces the expression of HaCTL3 via its receptor HaEcR−HaUSP complex.